Innovative Computational Intelligence: A Rough Guide to 134 Clever Algorithms - Xing, Bo; Gao, Wen-Jing (Intelligent Systems Reference Library, 2014)
The present book Innovative Computational Intelligence: A Rough Guide to 134 Clever Algorithms is compilation of recent trends in computational intelligence (CI) research using inspiration from various sources such as biology, physics, chemistry, and mathematics. Innovative CI, unlike its counterparts, i.e., highly developed and refined traditional CI, is a new CI category introduced in the present book. The major notable feature of this book is its innovation and comprehensiveness: 134 new paradigms of CI are covered and most of them are usually spread over a number of unrelated publishing directions. This book is useful to multidisciplinary students including such as aeronautic engineering, mechanical engineering, industrial engineering, electrical and electronic engineering, chemical engineering, computer science, applied mathematics, physics, economy, biology, and social science, particularly those pursuing postgraduate studies in advanced subjects. Moreover, the algorithms introduced in this book can motivate researchers to further develop more efficient and effective algorithms in dealing with many cutting-edge challenges that may sit on the periphery of their present fields of interest. Finally, practitioners can also use the models presented in this book as a starting point to solve and analyse specific real-world problems. The book is carefully written to achieve a good balance between the theoretical depth and the comprehensiveness of the innovative CI paradigms.